2008
DOI: 10.1530/eje-07-0663
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole once a week normalizes serum testosterone in obesity-related male hypogonadism

Abstract: Objective: Isolated hypogonadotropic hypogonadism (IHH) is frequently observed in severely obese men, probably as a result of increased estradiol (E 2 ) production and E 2 -mediated negative feedback on pituitary LH secretion. Aromatase inhibitors can reverse this process. This study evaluates whether letrozole once a week can normalize serum testosterone in severely obese men and maintain its long term effect. Design: Open, uncontrolled 6-month pilot study in 12 severely obese men (body mass indexO 35.0 kg/m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 45 publications
3
75
0
2
Order By: Relevance
“…The increased amount of estrogen levels might, in turn, play a negative feedback on both the hypothalamus and the pituitary, leading to decreased LH secretion (22,55). Accordingly, it has been reported that a weekly low dose (2.5 mg) of the aromatase inhibitor letrozole can restore testosterone levels and increase LH levels in severely obese hypogonadal men (57). In line with this view, we now show that body weight loss, obtained either by a lifestyle or bariatric intervention, is associated with a decline in estrogen levels and a rise in gonadotropins and testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…The increased amount of estrogen levels might, in turn, play a negative feedback on both the hypothalamus and the pituitary, leading to decreased LH secretion (22,55). Accordingly, it has been reported that a weekly low dose (2.5 mg) of the aromatase inhibitor letrozole can restore testosterone levels and increase LH levels in severely obese hypogonadal men (57). In line with this view, we now show that body weight loss, obtained either by a lifestyle or bariatric intervention, is associated with a decline in estrogen levels and a rise in gonadotropins and testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone replacement raises both serum testosterone and E 2 , whereas aromatase inhibitors induce a rise in testosterone but a decrease in E 2 (15). It appears that the expected beneficial effects of a rise in testosterone are offset by the decrease in estrogens.…”
Section: Aromatase Inhibition Vs Testosterone Replacementmentioning
confidence: 99%
“…Partial inhibition of aromatase activity is a more attractive approach, at least in theory. So far, two open-label, uncontrolled pilot studies have shown that the aromatase inhibitor letrozole can normalize serum testosterone and E 2 levels in OrHH (15). However, the clinical impact of this intervention is currently not known.…”
Section: Introductionmentioning
confidence: 99%
“…IHH is frequent in obese men, possibly as a consequence of enhanced aromatization of testosterone by aromatase, which is present in adipocytes in human (50). Treating obese men with an aromatase inhibitor restores normal testosterone levels (51). Some nonobese men also have excessive aromatase activity, possibly for genetic reasons, which results in nonobstructive azoospermia and low testosterone.…”
Section: Discussionmentioning
confidence: 99%